The Growth of Eimeria tenella: Characterization and Application of Quantitative Methods to Assess Sporozoite Invasion and Endogenous Development in Cell Culture - Marugan-Hernandez, Virginia; Jeremiah, Georgia; Aguiar-Martins, Kelsilandia; Burrell, Alana; Vaughan, Sue; Xia, Dong; Randle, Nadine; Tomley, Fiona (Frontiers in Cellular and Infection Microbiology, 2020)
In vitro development of the complete life cycle of Eimeria species has been achieved in primary cultures of avian epithelial cells with low efficiency. The use of immortalised cell lines simplifies procedures but only allows partial development through one round of parasite invasion and intracellular replication. We have assessed the suitability of Madin-Darby Bovine Kidney (MDBK) cells to support quantitative studies on sporozoite invasion and intracellular development (first-generation schizogony and merozoite production) of Eimeria tenella. Transmission electron microscopy (TEM) and serial block face - scanning electron microscopy (SBF-SEM) were used to evaluate the ultrastructure of developing schizonts, and parasite protein expression profiles of developing parasites were elucidated by mass spectrometry (MS). Using quantitative PCR and ImageJ semi-automated image analysis to track parasite development we demonstrate the suitability and reproducibility of the MDBK culture system and describe a series of methods and assays for the further application of this model for more complex studies on Eimeria including basic research on parasite cell biology and host-parasite interactions and for screening anticoccidial drugs.